Exploring The Purchase Intentions and Perceptions of Generation Z Towards Electric Vehicles in Jakarta: Insights and Recommendations - Wulandari, Hesti (Riviera Publishing, 2023)
This research aimed to explore the factors contributing to purchase intent towards electric vehicles (EVs) among Generation Z in Jakarta and their perceptions of electric vehicle marketing efforts from manufacturers and government programs. The study aimed to provide recommendations for manufacturers and the government to promote EVs through open-ended qualitative questionnaires, sentiment analysis from Twitter, and quantitative structural equation modelling. The open-ended qualitative questionnaire provided insights into Generation Z's purchase intention towards EVs, their knowledge and concern for environmental issues related to EVs, and their perceptions of marketing efforts from manufacturers and government programs. The sentiment analysis from Twitter revealed ositive sentiment towards electric cars, electric motorcycles, Hyundai Ioniq 5, and Wuling Air EVs. The quantitative structural equation modelling revealed that personal norms were a significant predictor of purchase intention, with a significant relationship between personal norms and environmental concern and peer effect. However, the relationship between environmental concern and peer effect on purchase intention was insignificant. Personal norms are a crucial factor in determining Generation Z's purchase intention of electric vehicles in Jakarta, and environmental concerns and peer effects have no significant effect. While Generation Z has a positive outlook on EVs, manufacturers, governments, and society need to do more to promote their adoption. Manufacturers should focus educating consumers about the benefits of electric vehicles, and governments should provide incentives to encourage their use. Further research is needed to investigate other factors influencing purchase intent, such as consumer knowledge and attitudes towards electric vehicles.